The Influence Of Perceptions Of Price And Quality Of Service On Purchasing Decisions On Tenteng Products PD. Kujang Jaya - Hidayat, Indra Ahmad; Lestari, Suci Putri; Wibawa, Gian Riksa (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of price perception and service quality simultaneously or partially on purchasing decisions for consumers of Tengteng PD Kujang Jaya products. The method used in this research uses quantitative methods. With a research sample of 100 people as respondents. Sampling uses non-probability, precisely using purposive sampling. And the analytical method used is multiple linear regression analysis, the results of the regression equation are Y=11.623 + 0.120X1 + 0.434X2 + e. Based on the research results, it shows that Price Perception is classified as Very Good, Service Quality is included in the Very Good classification, and Purchase Decisions are included in the Very Good classification. The test results show that simultaneously Price Perception and Service Quality have a significant effect on Purchasing Decisions. Partially, price perception does not have a significant effect on purchasing decisions and service quality has a significant effect on purchasing decisions.